Exploring classroom feedback interactions around EAP writing: A data based model. Issue 17 (March 2015) - Unlu, Zuleyha; Wharton, Sue M.
Abstract: This paper is based on case study research in the grounded theory tradition. In this paper we describe and theorise feedback interactions on EAP writing which were observed in classes in our institution. Working from detailed descriptions of feedback incidents and from interviews with teachers and students, we theorise a series of teacher and student actions. We argue that combinations of these actions are both reflective and constitutive of patterns of teacher–student relationships in the classes observed. Using interview data, we explore factors which may influence the nature of the actions and relationships which we have modelled. We also comment on the possible consequences for learners' ongoing understanding of academic writing. Highlights: There are relationship patterns in teacher-student feedback interactions on EAP writing. Each relationship pattern is constituted of actions deployed by teachers and students. Institutional self as displayed by teachers and students has an influence on the emerging relationship patterns. A possible impact of relationship patterns on learners is an increased critical awareness of academic writing.